RISK-ADJUSTED CAPITAL BUDGETING FOR CLINIC DEVELOPMENT INVESTMENT FEASIBILITY AT CAMAR MANDIRI JEMBER - Andre Rizal Sinaga; Irni Yunita (CV. Radja Publika, 2026)
This study evaluates the investment feasibility of developing Klinik Pratama Camar Mandiri Jember through a risk-adjusted capital budgeting approach. The project concerns the acquisition of land and an existing building, partial demolition, renovation, relocation, licensing, and initial working capital for a clinic that currently operates on leased premises. A descriptive-evaluative quantitative case study was conducted using 2020-2024 clinic financial statements, patient visit data, revenue and cost structures, investment budget assumptions, and indicative bank financing information. The analysis applies Net Present Value, Internal Rate of Return, Profitability Index, Payback Period, Discounted Payback Period, sensitivity analysis, scenario analysis, Monte Carlo simulation, and Debt Service Coverage Ratio. Under the base scenario, the project generates a positive NPV of IDR 311,469,830, IRR of 9.68%, PI of 1.13, and payback period of 12.36 years, indicating conditional economic feasibility. However, discounted payback exceeds 15 years, revenue growth is the most sensitive variable, the probability of positive NPV is 51.70%, and full bank financing is not supported by clinic cash flow. The investment is therefore feasible only with strict cost control, revenue stabilization, and prudent financing structure.